A Comparison of Safety, Health, and Well-Being Risk Factors Across Five Occupational Samples - Hanson, Ginger C.; Rameshbabu, Anjali; Bodner, Todd E.; Hammer, Leslie B.; Rohlman, Diane S.; Olson, Ryan; Wipfli, Brad; Kuehl, Kerry; Perrin, Nancy A.; Alley, Lindsey; Schue, Allison; Thompson, Sharon V.; et al. (Frontiers in Public Health, 2021)
Objective: The aim of this study was to present safety, health and well-being profiles of workers within five occupations: call center work (N = 139), corrections (N = 85), construction (N = 348), homecare (N = 149), and parks and recreation (N = 178). Methods: Baseline data from the Data Repository of Oregon's Healthy Workforce Center were used. Measures were compared with clinical healthcare guidelines and national norms. Results: The prevalence of health and safety risks for adults was as follows: overweight (83.2%), high blood pressure (16.4%), injury causing lost work (9.9%), and reported pain (47.0%). Young workers were least likely to report adequate sleep (46.6%). Construction workers reported the highest rate of smoking (20.7%). All of the adult workers reported significantly lower general health than the general population. Conclusion: The number of workers experiencing poor safety, health and well-being outcomes suggest the need for improved working conditions.